Relationship between jealousy emotional behaviors and violence against women (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
“Jealousy” is often associated in literature to violence against women perpetrated by their partners, presuming a causal relationship between them. Based on Behavior Analysis, a possible relation between these behaviors (“jealousy” and violence) was investigated through reports of 10 women sheltered in an institution of protection of violence victims who considered their partners jealous. Categories of analysis for the definitions of “jealousy” and the antecedents to the jealousy emotional responses were created, and contingency relations for each example of “jealousy” provided by the participants were drafted. One hundred percent of participants reported partner’s violent behavior when describing a situation of “jealousy” and all cited the suspicion of involvement with another person as antecedent to “jealousy”. The analysis led to the proposal of a different way of dealing with the relationship between “jealousy” and violence, considering the aggressive behavior of partners as a type (topography) of “jealousy”.
Keywords: jealousy; violence against women; behavior analysis